Influence of breed and environment on leukocyte telomere length in cattle - N. S. Yudin; A. V. Igoshin; G. A. Romashov; A. A. Martynov; D. M. Larkin (Вавиловский журнал генетики и селекции)
High milk yield is associated with reduced longevity in high-producing dairy cattle breeds. Pre-term culling leads to high replacement heifer demand and economic losses for the dairy industry. Selection for this trait is limited because of low heritability and difficulties in phenotype measurement. Telomeres are elements found at the ends of chromosomes, consisting of repetitive DNA sequences, several thousand base pairs in length, coupled with nucleoprotein complexes. Eventually, in humans and most other animals, telomere length reduces with age. When telomeric DNA is truncated to a critical length, cell ageing, cell cycle arrest, and apoptosis are induced. As a result, telomere length can be considered as a predictor of health risks and an individual’s lifespan. The leukocyte telomere length may be used as a proxy phenotype of productive lifespan to improve cattle selection. Our objectives were to assess the effects of breed and breed group (dairy vs. beef) on the leukocyte telomere length and to estimate the effect of cold climate on this trait in Kalmyk cattle populations from the South (Rostov Oblast) and Far North (Republic of Sakha) regions of Russia. The leukocyte telomere lengths were estimated computationally from whole-genome resequencing data. We leveraged data on leukocyte telomere length, sex, and age of 239 animals from 17 cattle breeds. The breed factor had a significant effect on leukocyte telomere length across our sample. There was no difference in leukocyte telomere length between dairy and beef groups. The population factor had a significant effect on leukocyte telomere length in Kalmyk animals. In conclusion, we found that breed, but not breed group (dairy vs. beef), was significantly associated with leukocyte telomere length in cattle. Residence in colder climates was associated with longer leukocyte telomere length in Kalmyk breed cattle.